CRISPR/Cas9-mediated knockin of human factor IX into swine factor IX locus effectively alleviates bleeding in hemophilia B pigs - Chen, Jiahuan (Haematologica, 2020)
Hemophilia B is an X-linked recessive bleeding disorder caused by abnormalities in the coagulation factor IX gene. Without prophylactic treatment, patients experience frequent spontaneous bleeding episodes. Well-characterized animal models are valuable for determining the pathobiology of the disease and for testing novel therapeutic innovations. Here, we generated a porcine model of hemophilia B (HB) using a combination of CRISPR/Cas9 and somatic cell nuclear transfer. We also tested the possibility of HB therapy by gene insertion. Frequent spontaneous joint bleeding episodes that occurred in HB pigs allowed a thorough investigation of the pathological process of hemophilic arthropathy. In contrast to the HB pigs, which showed a severe bleeding tendency and joint damage, the transgenic pigs carrying human coagulation factor IX exhibited a partial improvement in bleeding. In summary, this study not only offers a translational HB model for exploring the pathological process of hemophilic arthropathy, but also provides a possibility for the permanent correction of hemophilia in the future by genome editing in situ.